2021
DOI: 10.1002/cmdc.202100334
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy‐Dependent Ferroptosis as a Therapeutic Target in Cancer

Abstract: Ferroptosis is an iron-dependent form of cell death associated with the accumulation of labile iron and cytotoxic lipid peroxides. Increasing evidence reveals that ferroptosis is not a self-standing phenomenon and has close connections with other cellular events. Remarkably, recent insights show that ferroptosis is dependent on autophagy, which is a lysosomal degradation pathway responsible for the recycling of damaged cellular components under survival stress. Autophagy is capable of contributing to ferroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 126 publications
(73 reference statements)
0
23
0
Order By: Relevance
“…Disordered lysosomes recruit undigested substances, which ultimately contribute to lysosomal storage dysfunction. Recently, researchers have pointed out that lysosomes play a significant role in the formation of ferroptosis [ 74 – 76 ]. First, lysosomes are the major storage location for iron [ 77 ].…”
Section: The Fundamental Roles Of Organelles In Ferroptosismentioning
confidence: 99%
“…Disordered lysosomes recruit undigested substances, which ultimately contribute to lysosomal storage dysfunction. Recently, researchers have pointed out that lysosomes play a significant role in the formation of ferroptosis [ 74 – 76 ]. First, lysosomes are the major storage location for iron [ 77 ].…”
Section: The Fundamental Roles Of Organelles In Ferroptosismentioning
confidence: 99%
“…In a previous report, ferroptosis was originally defined as a programmed cell death distinct from autophagy, apoptosis, and necrosis [ 7 ]. However, recent insights suggest that ferroptosis is not a self-standing phenomenon and has close connections with other cellular events [ 50 ]. For example, ferroptosis dependents on autophagy, especially selective types of autophagy, through direct or indirect regulation of iron accumulation or lipid peroxidation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent insights suggest that ferroptosis is not a self-standing phenomenon and has close connections with other cellular events [ 50 ]. For example, ferroptosis dependents on autophagy, especially selective types of autophagy, through direct or indirect regulation of iron accumulation or lipid peroxidation [ 50 , 51 ]. The top KEGG result is cytokine−cytokine receptor and the top 2 GSEA results are the hallmark gene sets of TNF α signaling via NF- κ B and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, an iron-related form of cell apoptosis, is defined as the accumulation of iron and cytotoxic lipid peroxides [ 155 ]. It was recently demonstrated that ferroptosis is related to autophagy through the degradation of ferritin, accompanied by an increment in intracellular iron and lipid ROS.…”
Section: The Role Of Autophagy In Cancermentioning
confidence: 99%
“…It was recently demonstrated that ferroptosis is related to autophagy through the degradation of ferritin, accompanied by an increment in intracellular iron and lipid ROS. The link between autophagy and ferroptosis may give rise to future anticarcinogenic treatment options [ 155 ]; however, more research is warranted to further elucidate this issue.…”
Section: The Role Of Autophagy In Cancermentioning
confidence: 99%